INFLUENCE OF CLUSTERS ON EMPLOYMENT IN THE REGIONS - O. Kazeeva (Вестник университета)
Today clusters are one of the most discussed subject in the international economy cause clusters have a powerful influence on competitive ability of region economics. In the article cluster is considerated as factor, which have an inmact on employment in the country. The resumes of employment multiplier overview for Indiana State are presented. The survey was realized about need for government involvement in a cluster evolution and functioning. In the article the author develops a hypothesis clusters in Russia would be cause of decline in unemployment.